The Threat of New Colonialism and the Ethical Crisis of Balinese Tourism - Dananjaya, Ahmad Ghazy (Prasetiya Mulya Publishing, 2025)
This study investigates how the increasing foreign property dominance in Canggu, Bali, fueled by a post-pandemic surge in digital nomads, is pushing aside tourism ethics. This influx has created an unprecedented demand for villas and co-working spaces, leading to a severe land crisis and heightened social inequality. The conversion of agricultural land into tourism properties, often ignoring sustainability, directly threatens Bali's food security and significantly damages vital local ecosystems, including the UNESCO-recognized traditional Subak irrigation system. Moreover, the escalating influence of foreign investors worsens existing social and economic disparities while intensifying the erosion of Balinese culture. Drawing on data from 400 respondents, this research proposes actionable solutions: a moratorium on commercial property permits in green zones, agricultural land rehabilitation, empowerment of the local economy, and stringent enforcement of customary law. Our policy recommendations highlight the critical need for sustainable tourism planning and robust property regulations to safeguard environmental and cultural sustainability. This study aims to deepen the understanding of more responsible and sustainable tourism practices in Bali and other regions grappling with similar developmental challenges.